EFFECT OF SOWING TECHNIQUES ON YIELD AND RAINFALL PRODUCTIVITY PEARL MILLET INGARDUD SOIL OF NORTH KORDOFAN STATE - hassan, sawsan kamal (Journal of Agricultural Sciences (Belgrade), 2020)
Pearl millet is grown in environments that are prone to drought and most vulnerable to climate change. The stresses and variability of the rain fed dry lands that are further exacerbated by climate change, a different approach is needed, for  adapts to environmental variability and risks. Pearl millet is the cereal crop that had great potential for ensuring food security and income generation in marginal areas because of its suitability to the extreme limits of agriculture. This study was carried at Jebel Kordofan experimental site, Sheikan province in North Kordofan state during 2010 -2013 seasons to evaluate the effect of different sowing techniques on yield and rainfall productivity of local and improved millet cultivars. Treatments were combination of four sowing techniques and two cultivars of pearl millet. The sowing techniques were; dry sowing , wet sowing , deep dibbling (10 cm depth) and priming with micro dozing fertilizer. The two cultivars were Ashana (improved) and Dembi (local). These treatments were arranged in split plot design, main plot for cultivars and subplot for sowing methods in four replications. The parameters studied were days to 50% flowering, plant height (cm), grain yield (kg/ha) and rainfall productivity (kg/ha/mm). The cultivars showed highly significant differences in number of days to 50% flowering, plant height (cm),grain yield( kg/ha) and rainfall productivity  (kg/ha/mm).The dry sowing technique significantly (P ≤ 0.05) produced the tallest plant (149cm), higher water use efficiency (5.10 kg/ha/mm) and highly significantly produced the highest grain yield (1637 kg/ha). It can be concluded from these results that seed bed prepared with chisel plough and sown on dry produced the highest grain yield